1997
DOI: 10.1002/(sici)1097-4652(199707)172:1<36::aid-jcp4>3.3.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Human umbilical vein endothelial cells express high affinity receptors for factor Xa

Abstract: The binding of [125I]-factor Xa to human umbilical vein endothelial cell (HUVEC) monolayers was studied. At 7 degrees C, [125I]-factor Xa bound to a single class of binding sites with a dissociation constant value of 6.6 +/- 0.8 nM and a binding site density of 57,460 +/- 5,200 sites/cell (n = 3). Association and dissociation kinetics were of a pseudo-first order and gave association and dissociation rate constant values of 0.15 x 10(6) M-1 s-1 and 4.0 x 10(-4) s-1, respectively. [125I]-factor Xa binding was i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
17
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 0 publications
2
17
0
Order By: Relevance
“…Factor Xa acts as a potent mitogen for endothelial cells (23), fibroblasts (24), and vascular SMCs (25,26). Both proteases can also elicit endothelial cell and SMC migration through pro-MMP-2 activation and subsequent extracellular matrix degradation (13,27,28).…”
mentioning
confidence: 99%
“…Factor Xa acts as a potent mitogen for endothelial cells (23), fibroblasts (24), and vascular SMCs (25,26). Both proteases can also elicit endothelial cell and SMC migration through pro-MMP-2 activation and subsequent extracellular matrix degradation (13,27,28).…”
mentioning
confidence: 99%
“…In endothelial cells addition of FXa can activate NO synthase (13,14) and induce synthesis of cytokines and expression of adhesion molecules (14,15). Antibodies to PDGF (11,16,17) or effector cell protease receptor-1 (EPR-1) (17,18) both attenuate mitogenic responses to FXa in endothelial cells and in vascular smooth muscle cells. Factor V (FV), the cellular cofactor for FXa in formation of the prothrombinase complex (2), has to our knowledge not been shown to participate in any of these events.…”
mentioning
confidence: 99%
“…This protein, called effector protease receptor-1 (EPR-1), behaves as a cofactor for factor Xa to catalyze prothrombin activation in the absence of added factor Va. 2 Recently, we and others demonstrated the existence of such a population of high-affinity, functional, factor Xa-binding sites in human vascular endothelial cells (HUVECs) and showed that exposure of HUVECs to factor Xa induced phosphoinositide turnover and an increase in intracellular free Ca 2ϩ . 3,4 Most important, through binding to this receptor, factor Xa was also a potent mitogen for endothelial cells. 3 Moreover, a recent article by Papapetropoulos et al 5 showed increased interleukin-6 release by HUVECs after treatment with factor Xa.…”
mentioning
confidence: 99%
“…3,4 Most important, through binding to this receptor, factor Xa was also a potent mitogen for endothelial cells. 3 Moreover, a recent article by Papapetropoulos et al 5 showed increased interleukin-6 release by HUVECs after treatment with factor Xa. These activities of factor Xa are affected by selective factor Xa inhibitors, which suggests that occupancy of EPR-1 alone by factor Xa is not sufficient for cell activation and that protease activity is required for factor Xa to induce signal transduction and subsequent activation of vascular endothelial cells.…”
mentioning
confidence: 99%